ASPEK PIDANA TENTANG PELAKSANAAN PEMBERIAN BANK GARANSI DI PT. BANK EKONOMI RAHARJA CABANG SEMARANG MENURUT UNDANG-UNDANG NO 10 TAHUN 1998 DAN SURAT KEPUTUSAN BANK INDONESIA NO. 23 TAHUN 1991 - TJIANGDI, TJIANGDI (Dinamika Hukum, 2016)
The purpose of a study to assess and analyze the implementation of theprovision of bank guarantee in PT. Bank Ekonomi Raharja Semarang Branch,knowing the causes of default and how to handle the implementation of theprovision of a bank guarantee in Bank Ekonomi Raharja, and examine thecriminal aspects in the conduct of the administration of the bank guarantee inBank Ekonomi Raharja.Background is based on interviews of researchers with PT BankEkonomi Raharja found in cases where there are customers who default so thatthis becomes an interesting topic for research. In the activities of Bank Guarantee,customers can take advantage of a bank guarantee to provide as collateral to BankEkonomi Raharja as required by suppliers used to guarantee payment of suchwork so that the reliability of the implementation of the work is quite secured by abank guarantee. Based on the above it is necessary to do research on the processof judicial practice in awarding the bank guarantee and the completion of the bankin the practice of the implementation of the provision of a bank guarantee.The research method consisted of: This research type is JuridicalEmpirical approach, that is an approach method used to solve the research objectby examining secondary data to primary data in the field.Conclusion. Implementation of a bank guarantee in Bank EkonomiRaharja in accordance with the regulations of Bank Indonesia concerning theprovision of bank guarantee by Bank Ekonomi Rahardja. Because of default andhow to overcome them in the implementation of the provision of a bank guaranteein Bank Ekonomi Raharja is a debtor bankrupt and release all the privileges by thebank. But during the time in Bank Ekonomi Raharja new branch will not occur orhave occurred yet significant problems associated with the provision of a BankGuarantee to its customers. There are criminal aspects in the implementation ofthe provision of a bank guarantee in Bank Ekonomi Raharja related to Article 378of the Criminal Code.Keywords: Bank warranty, tort, criminal aspect.